Predicting Factors of Perceived 21st Century Competency Among Nursing Students - Rungruang, Jitprapa; Suwannawung, Siriluk (Nursing Journal CMU, 2024)
21st century competency refers to important characteristics and skills that enable and improve learning of nursing students which leads to learning outcomes development according to the National Higher Education Qualifications Framework. This competence is composed of five aspects: 1) capacity to communicate, 2) capacity to think, 3) capacity to perform problem-solving, 4) capacity for applying life skills, and 5) technological compe- tency. This predictive correlational research aimed to investigate the predictive ability of selected factors on nursing students’ competency. The participants consisted of 144 nursing students who were currently studying at the Buri Ram Province private university in their 1st to 4th years. Stratified random sampling was used to recruit samples. The instruments consisted of 1) a demographic data record form (age, gender, grade point average, family monthly income, and monthly income from family), 2) the SPST 20 stress questionnaire, and 3) the nursing students’ perceived 21st century competency questionnaire. Data was analyzed using descriptive statistics, Pearson correlation coefficient, and stepwise multiple regression equations. The results revealed that participants’ overall perceived 21st century competency was at a high level (M = 1.35, SD = 0.39). Students’ college year and their monthly income from family were statistically significantly correlated with their perceived 21st century compe- tency (r = -.016, p < .01; and r = .106, p < .01, respectively). Nevertheless, college year (β = -.136, p < .001) and monthly income from family (β = .031, p < .001) statistically significantly predicted perceived 21st century competency at 6.6% (R2 = .066, F (df1= 2, df2 = 141) = 1.291, p < .001). The results of this study can be used as basic information to enhance the 21st century competency of nursing students.